Transcutaneous Retrobulbar Amphotericin B (TRAMB) injection in acute invasive Rhino-Orbital-Cerebral Mucormycosis (ROCM) - Chan SY; Ng QX; Sylves Patrick; Hanida Hanafi (Kugler Publications, 2025)
ROCM is a rare and life-threatening infection in immunocompromised hosts, marked by vascular thrombosis and poor antifungal penetration. Treatment involves antifungals, surgical debridement, and immune restoration. While exenteration is standard for severe cases, several studies proposed TRAMB as a promising adjunct to reduce its necessity.